American star [videorecording (DVD)] - Faerna, Nacho; McShane, Ian, 1942-; Arnezeder, Nora, 1988-; Nagaitis, Adam; Gertrúdix, Andrés, 1977-; Coleman, Oscar; Arán, Sabela; Kretschmann, Thomas, 1962-; Ardant, Fanny (IFC Films, 2024)
An assassin on final assignment arrives in Fuerteventura to kill a man he has never met. But the target is delayed. Instead of following protocol he stays, drawn to the island, the people, and a ghostly shipwreck. When the target returns, the world has shifted. Before everything was simple, now nothing is.